Failure analysis of a Portuguese cultural heritage masterpiece: Bonet building in Sintra. (September 2020) - Malcata, Madalena; Ponte, Madalena; Tiberti, Simone; Bento, Rita; Milani, Gabriele
Highlights: Failure analysis with advanced numerical FE computing on an outstanding historical palace. Utilization of full 3D FE non-linear dynamic analyses to reproduce damage. Comparison between non-linear static behaviour of a 3D model and equivalent frame. Damage-plasticity with softening in tension and compression material used to model masonry. N2 method to assess vulnerability after preliminary modal analysis. Abstract: The paper addresses the failure analysis under horizontal loads of the most ancient body of the National Palace of Sintra, Portugal: the Bonet building. This is a URM construction built on top of Arabic foundations during the reign of King Denis of Portugal around 1281; since then, few alterations have been made to the building. Due to the exemplary conservation of the whole palace, a few crack patterns are identified only on the top floor of the Bonet building, an area that is not open to visitors and that will soon undergo restoration works. The seismic vulnerability assessment of this building is carried out following two different approaches, enacted in two distinct numerical models: the so-called Equivalent Frame Method (EFM) and the Finite Element Method (FEM) developed in 3Muri and ABAQUS software, respectively. Both approaches adopt a numerical procedure based on the use of nonlinear static analyses, introducing "equivalent" boundary conditions that are defined to consider, approximately and conventionally, the possible interaction effects among the different parts of the structure. To minimize the multiple uncertainties usually existing in complex masonry buildings, whether related to geometry or masonry mechanical properties, a detailed structural survey is conducted through the laser scanning technology as well as in situ experimental tests. Different types of experimental tests are carried out, both non- and semi-destructive, including a Ground Penetrating Radar test, ambient vibration tests, flat-jack tests, and the collection of masonry samples. All these tests are important to adequately characterize the building and to calibrate the numerical models. Moreover, these tests enable the extraction of values for the mechanical properties of the rubble stone masonry that are used in the later numerical simulations on the Bonet building and, most importantly, can be used as a reference for future works regarding historical Portuguese monuments of the same period. Afterwards, the results obtained from the nonlinear static analyses with the two different software 3Muri and ABAQUS are presented and discussed. Specifically, the differences in modelling strategies and characterization of materials between the two software are considered with special regard to their feasibility, required computational effort, data availability and applicability to large scale structures. Efforts to calibrate and obtain the same behavior of the building for the different software are made, involving geometry, boundary conditions and characterization of the material constitutive laws. Eventually, a nonlinear dynamic analysis is carried out in ABAQUS to further assess the seismic vulnerability of the Bonet building; a spectrum-compatible accelerogram is applied to the numerical model, and the time-history of displacements in relevant control points of the buildings are extracted and discussed.